A system dynamics model for emissions projection of hinterland transportation. (1st May 2019) - Liu, Pei; Liu, Chao; Du, Jianbang; Mu, Dong
Abstract: The rapid development of China's economy has led to a rapid increase in port throughput and made the issue of hinterland transport emissions more prominent. In this paper, a system dynamics model was established to project the long-term emissions of hinterland transportation. The model functions in a modular manner, consisting of core subsystems developed based on the classic four-step model of transportation, and several additional subsystems that are used to address the characteristics of the hinterland transport processes. The developed model was applied to a specific case in China to assess the long-term effects of alternative environmental policies on hinterland transport emissions. Through a comprehensive comparison of different policy scenarios, the model demonstrates explicitly how alternative environmental policies affect long-term emissions through a systematic intervention on a series of hinterland transport processes. The model also identifies the effective policies by which a lower emissions stock could be achieved. In addition, some suggestions for the policy making in hinterland transportation are provided. Graphical abstract: Image 1009 Highlights: Some unique characteristics of hinterland transport processes are considered. System dynamics modeling for long-term hinterland transport emissions projection. Alternative modal shift policies are considered and compared by the model. Policies' effects on both hinterland transport processes and emissions are shown. The policies that effectively reduce hinterland transport emissions are identified.